INTERDISCIPLINARY CORRELATION AND INTEGRATION OF NATIVE LANGUAGE READING LITERACY - Boyburiyeva Shaxrida Kasim’s daughter (Sciental Journals Publishing, 2025)
This article will talk about the role of native language Reading Literacy in reading and understanding other subjects, the development of speech, the development of skills in other areas, knowledge of the language and the necessary basic tool in its effective use.
Keywords: Methodology, terminology, speech, critical thinking, analysis, logic, creative thinking, linguistics, didactics, understanding, national program.